Literature Review: Biological Monitoring of Occupational Tetrachloroethylene Exposure in Workers - Dina Tri Amalia; Muhammad Ilyas (Universitas Airlangga, 2021)
Introduction: One of the most common chlorinated solvents in the world is tetrachloroethylene (TCE) because it is widely used in various industries. Exposure to tetrachloroethylene can cause health problems so biological monitoring is necessary to do. The aim of this research is to assess which one is more feasible to use among the various types of biological monitoring for tetrachloroethylene exposure, based on the evidence-based literature. Methods: The literature searching was performed via electronic databases from PubMed, Scopus, and Proquest. The keywords used were “biological monitoring”, “biomonitoring”, “tetrachloroethylene”, “perchloroethylene”, “work” and “occupation”. The articles were chosen based on the given inclusion and exclusion criteria. Selected articles were then critically appraised. Results: Initially 29 papers were collected, but only6 cross-sectional articles were selected after the screening process and manual searching. Based on the selected evidence-based literatures, statistically meaningful associations were found between tetrachloroethylene exposure and tetrachloroethylene in blood in pre- and end-of-shift, in urine at end of shift, and in exhaled air at end-of-shift. Moreover, micronucleus frequency and DNA damages between dry cleaning workers and the controls differed significantly. Conclusion: The level of tetrachloroethylene in blood, urine, and exhaled air becomes an appropriate biological exposure index for assessing tetrachloroethylene exposure in dry-cleaning workers. In Indonesia, biomonitoring that is more feasible to be implemented is micronucleus frequency evaluation from buccal mucosal epithelial smears since it is a simpler, faster, and less expensive procedure.Keywords: biological monitoring, biomonitoring, occupational exposure, tetrachloroethylene